1981
DOI: 10.1093/nar/9.5.1219
|View full text |Cite
|
Sign up to set email alerts
|

The interaction of polyamines with DNA: a23Na NMR study

Abstract: The interaction between a variety of polyamines, both naturally occurring and synthetic, and calf thymus DNA has been studied using 23Na NMR. The relaxation behaviour of 23Na reflects the extent of interaction of Na+ with DNA phosphate groups and therefore the extent of charge neutralisation of DNA phosphate groups (P) by polyamine amino and imino groups (N) in solutions of DNa, polyamine and Na+. The studies reveal that whereas spermine and spermidine are capable of expelling nearly all of the Na+ ions from D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

1984
1984
2007
2007

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(13 citation statements)
references
References 26 publications
0
12
0
1
Order By: Relevance
“…The trivalent spermidine analogs are of interest in this context and have been employed in several physicochemical studies (12)(13)(14). Definite structural effects have been observed in DNA condensation, thermal helix-coil transition and B-Z transition (12,14,48,49). Thus, the simple counter ion condensation theory does not account for the structural specificity of cations seen in the current study and by others.…”
Section: Discussionmentioning
confidence: 72%
“…The trivalent spermidine analogs are of interest in this context and have been employed in several physicochemical studies (12)(13)(14). Definite structural effects have been observed in DNA condensation, thermal helix-coil transition and B-Z transition (12,14,48,49). Thus, the simple counter ion condensation theory does not account for the structural specificity of cations seen in the current study and by others.…”
Section: Discussionmentioning
confidence: 72%
“…X-ray studies (Liquori et al, 1967;Quigley et al, 1978;Drew and Dickerson, 1981;Kopka et al, 1983;Jain et al, 1989) have shown several types of polyamine binding sites on nucleic acids. In contrast to the X-ray results, DNA-polyamine interactions in solutions studied by nuclear magnetic resonance (NMR) are most simply interpreted as a nonspecific and mainly electrostatic association (Burton et al, 1981;Wemmer et al, 1985;Braunlin et al, 1986;Padmanabhan et al, 1988;Besley et al, 1990;Padmanabhan et al, 1991). It should be noted that in general the development and application of polyelectrolyte theories to the interaction of multivalent cations with DNA have not been very frequent, and this is particularly evident in the case of polyamines.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have concluded that polyamines interact with DNA in a non-sequence-specific manner (1517). Furthermore, polyamines stabilize both duplex and triplex B-DNA structures (18), as well as A-form DNA and also promote B- to Z-DNA transitions of certain sequences (19,20).…”
Section: Introductionmentioning
confidence: 99%